PENGARUH VARIABEL FUNDAMENTAL TERHADAP HARGA SAHAM (Studi Pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Badillah, Iqlima Kian (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to determine the effect of Fundamental Variables on stock prices of property and real estate companies listed on the Indonesia Stock Exchange period 2011 to 2015. The variables used in this study are Earning Per Share (EPS), Price Earning Ratio (PER), Debt To Equity Ratio (DER), Return On Equity (ROE), Dividend Per Share (DPS). The type of research used is explanatory research.Population in this research is property and real estate company listed in BEI period 2011 to 2015 hours amounted to 47 by using purposive sampling method, obtained by research sample as many as 13 companies. The analysis method used is multiple linear regression analysis and hypothesis testing is done by using f test and t test.The results showed that the variables EPS, PER, ROE, and DPS partially have a significant positive effect on stock prices. While the DER variable does not significantly influence the negative direction of stock prices. EPS, PER, DER, ROE, and DPS simultaneously affect the stock price is 79.7% the remaining 20.3% is influenced by other variables outside the five independent variables studied. The most influential variable to stock price is PER variable with standardized coefficients beta equal to 0,521.Keywords: Stock price, Earning Per Share, Price Earning Ratio, Debt To Equity Ratio, Return On Equity, Dividend Per Share